Pengaruh Kualitas E-Government terhadap Kepuasan Pengguna E-Filing Studi Kasus Wajib Pajak OP di Surakarta Tahun 2019 - Gunawan Setyo Utomo (JURNAL PUNDI, 2020)
This study aims to determine the effect of system quality, information quality, and service quality on E-filing user satisfaction in Surakarta. The population and sample in this study are individual taxpayers registered at the Pratama Surakarta Tax Office in 2019. The data collection technique of this study uses incidental sampling techniques, and the determination of the number of samples using Slovin formula with a sample of 100 respondents. The data used in this study is a questionnaire using a Likert scale 1 to 5. The data analysis technique used in this study is multiple linear regression. Based on the results of the analysis conducted, it shows that there is a positive influence on system quality and service quality on E-filing user satisfaction. While the quality of information does not affect E-filing user satisfaction.Keywords: System Quality, Information, Services, User Satisfaction